Computer aided and experimental study of cinnamic acid analog for oxidative stress treatment: The therapeutic validations. (2022) - Ojo, Oluwafemi Adeleke; Ogunlakin, Akingbolabo Daniel; Iyobhebhe, Matthew; Olowosoke, Christopher Busayo; Taiwo, Odunayo Anthonia; Akinola, Akolade; Fadiora, Daniel; Odugbemi, Adeshina Isaiah; Gyebi, Gideon Ampoma; Nwonuma, Charles Obiora; Ojo, Adebola Busola; Ojo, Omolara Olajumoke
Abstract: Objectives: The purpose of this study was to investigate the therapeutic activity of the cinnamic acid derivative KAD-3 (ethyl 3-(4-methoxyphenyl) acrylate) on Fe 2+ -induced oxidative hepatic damage via experimental and computer aided studies. Methods: Oxidative hepatic damage was induced via incubation of tissue supernatant with 0.1 mM FeSO4 for 30 min at 37 °C ex vivo with different concentration of KAD-3. Molecular docking, ADMET profiling, and density functional theory were conducted on the candidate to filter the properties of the drug candidate for drug design. Key findings: GSH, CAT, and ENTPDase activities were reduced when hepatic damage was induced (p < 0.05). In contrast, a significant increase in MDA levels and an increase in ATPase activity were observed. When compared to control levels, KAD-3 treatment reduced these levels and activities (p < 0.05). KAD-3 demonstrated good bond formation (−5.8 kcal/mol, −5.6 kcal/mol), drug-likeness (no rule violation), and electronic properties (chemically reactive) as compared to the standard (quercetin). Molecular docking, ADMET profiling, and density functional theory predict the functional attributes of the drug candidate against ATPase and ENTPDase targets. Conclusion: The findings from our study indicated that KAD-3 can protect against Fe 2+ -induced hepatic damage by suppressing oxidative stress and purinergic activities.